Analiza svetovnih-sistemov in formalizem v literarni zgodovini - Habjan, Jernej (Slavistična revija, 2011)
A decade after Franco Moretti's plea for the distant reading of world literature, its critiques are culminating in, say, Michael Holquist's dismissal of distant reading on behalf of Jakobsonian philology. Distant reading, however, can indeed be charged with denouncing close reading, but not Jakobson. The formal "jumps" reconstructed by Moretti via quantitative analyses of the longue durée of forms activate what Roman Jakobson calls the "poetic function of language". Moreover, Jakobson is ignored by the very historiography that confronts Moretti's theory of world literature with local literary facts that are said to deserve canonisation. These critiques fail to see that theories can be falsified only by stronger theories, not by facts, and tha t Moretti's local facts not in the core's canon, but in the peripheries exploited by the core, may be a good starting point.
Keywords: branje; history of literature; Jakobson, Roman, 1896-1982; literarna teorija; literarna zgodovina; literary theory; Moretti, Franco, 1950-; natančno branje; oddaljeno branje; strukturalna poetika